Hybrid Graphene Titanium Nanocomposites and Their Applications in Energy Storage Devices: a Review - Heng I.; Low F.W.; Lai C.W.; Juan J.C.; Tiong S.K. (Springer, 2023)
Carbon dioxide; Electric charge; Electric energy storage; Electrodes; Electrolytes; Electrolytic capacitors; Fossil fuels; Gas emissions; Graphene; Graphene devices; Nanocomposites; Supercapacitor; TiO2 nanoparticles; Titanium dioxide; Electricity generation; Electricity storages; Electroactive material; Formation mechanism; Reduced graphene oxides; Specific capacitance; supercapattery; Various technologies; Storage (materials)